Mechanisms of Hepatitis B Virus Persistence - Tsai, Kuen-Nan; Kuo, Cheng-Fu; Ou, Jing-Hsiung James (Trends in microbiology (Regular ed.), 2018)
Hepatitis B virus (HBV) chronically infects 250 million people worldwide, resulting in nearly one million deaths annually. Studies in recent years have significantly improved our knowledge on the mechanisms of HBV persistence. HBV uses multiple pathways to harness host innate immunity to enhance its replication. It can also take advantage of the developing immune system and the not-yet-stabilized gut microbiota of young children to facilitate its persistence, and use maternal viral e antigen to educate immunity of the offspring to support its persistence after vertical transmission. The knowledge gained from these recent studies paves the way for the development of new therapies for the treatment of chronic HBV infection, which has so far been very challenging. HBV frequently causes chronic infection after vertical transmission but mostly self-limited acute infection after horizontal transmission. HBV harnesses type I interferon immune response to enhance its own replication. HBV persistence is affected by the age of infection, size of viral inoculum, and gut microbiota. Maternal HBeAg can train Kupffer cells of the offspring, likely in utero, to suppress HBV-specific CD8+ T cells in the presence of HBeAg after birth.